SOME REASONS WHY PHYSICAL EDUCATION TEACHERS DO NOT HAVE A HIGH ENOUGH LEVEL OF PROFESSIONAL AND PEDAGOGICAL KNOWLEDGE - Akhmedova, Fotima (Journal of Contemporary World Studies, 2024)
The article will talk about the inadequacy and main reasons for the pedogogical knowledge of specialists in the field of physical education sports , a number of pedogogical problems in the organization of the lesson and training of physical education.